CDK4/6 inhibitors in breast cancer: is it possible to predict response? - Soldi, Nathália Machado; Gouvea, Lucas de Amorim; Souza, Viviane Primo Basílio de; Sanches, Solange Moraes; Lima, Vladmir Claudio Cordeiro de; Leite, Luciana de Moura; Santos, Elizabeth Santana dos (Mastology, 2026)
Introduction: Up to 20% of luminal breast cancer patients present recurrent disease within ten years. The development of cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6) has transformed treatment paradigms due to significant improvements in outcomes. However, no predictive biomarker has been identified despite extensive translational research. Additionally, evidence on CDK4/6 efficacy in specific populations (e.g., pathogenic germline carriers) and clinical scenarios (treatment sequencing, combinatorial strategies, and post-CDK4/6 therapy) remains limited. Objective: This study aimed to review clinical, histological, and genomic profile searching for predictive variables of better responses. Methods: This is a retrospective study of luminal breast cancer patients treated with three available CDK4/6: abemaciclibe (AB), ribociclib (RIB), and palbociclib (Pb), between 2018 and 2024. Results: A total of 378 patients were included, with a median age of 60 years; 38% were pre-menopausal. Median progression-free survival (PFS) and overall survival (OS) were 30 and 56 months (m), respectively. Most (65%) received CDK4/6 in 1L, 15% in 2L, and 20% in later lines. PFS and OS declined progressively: 1L (36/62m), 2L (22/52m), others (14/33m) (p<0.01). No significant PFS (p=0.96) or OS (p=0.42) differences were observed between CDK4/6 (AB 24/43m; RIB 25/45m; PB 27/45m). Patients with visceral metastasis had worse PFS/OS (28 vs. 32m, p=0.009; 49 vs. 60m, p=0.01). High Ki67 (>70%) predicted poorer outcomes (PFS 15 vs. 29m, p=0.009; OS 34 vs. 56m, p=0.017). Conclusion: These results may help refine patient selection and therapeutic strategies and serve as a basis for prospective studies aiming to validate predictive biomarkers in hormone receptor-positive metastatic breast cancer.